Short Term Outcome Of Macrosomic Neonates Of Diabetic & Non-Diabetic Mothers - Hameed, Numan N.; Mtasher, Esraa M. (Journal of the Faculty of Medicine Baghdad, 2013)
Background: Big birth weight is one of the important factors affecting the perinatal morbidity & mortality. It may result in an irreversible squeal because of birth trauma & fetal asphyxia. Patients & Methods: This is a prospective study of 50 singleton macrosomic newborns weighting 4000 g & more aged 1-3 days admitted in the neonatal care unit of Children Welfare Teaching Hospital & Baghdad Teaching Hospital during a 6 months period from 1st of March to 1st of September 2010. The maternal & neonatal records were reviewed & infant morbidities including hypoglycemia, respiratory distress, feeding intolerance, birth injury & associated anomalies were discussed. All the infants were followed until they were discharged from the hospital.Objectives: to compare the short term outcomes of macrosomic infants born to diabetic and non-diabetic mothers. Results: Infants of diabetic mothers (52%) were more likely to develop neonatal morbidity compared to infants of non diabetic mothers (48%), these include hypoglycemia (76.9% vs. 8.3%), Respiratory distress (61.5% vs. 37.5%), and birth injury (7.7% vs. 4.2%) & nearly equal incidence of feeding intolerance (11.5% vs. 12.5%). Associated anomalies especially congenital heart disease (10%) found in infant of diabetic mothers only. Conclusions: Most of birth weight variation remains unexplained & most non-IDM macrosomic infants do not have identifiable risk factors. Macrosomia is generally associated with neonatal morbidity & neonatal injury. The potential dangers of birth injury in vaginal delivery have increased the rates of cesarean section to (68%). Infants of diabetic mothers have a higher rate of neonatal morbidity overall including hypoglycemia, respiratory distress, birth injury & congenital heart disease.